Topical delivery of 4-hexylresorcinol promotes wound healing via tumor necrosis factor-α suppression. Issue 7 (November 2016) - Ahn, Janghoon; Kim, Seong-Gon; Kim, Min-Keun; Kim, Dae-Won; Lee, Jang-Ha; Seok, Hyun; Choi, Je-Yong
Highlights: Burn wound healing mechanism for 4-hexylresorcinol (4HR) is proposed. The expression of TNF-α was inhibited by 4HR in RAW264.7 cells. The ointment containing 4HR displayed less TNF-α expression after burn. The 4HR contained ointment showed rapid epithelization. Abstract: Objective: The objective of this study was to evaluate (1) the effect of 4-hexylresorcinol (4HR) application on TNF-α expression in RAW264.7 cells and (2) the effect of 4HR ointment on burn wound healing in a rat burn wound model. Materials and methods: RAW264.7 cells were cultured in the presence of different concentrations of 4HR, and the attached cells were sampled for western blot analysis at each time point. Animal studies were conducted on male Wistar rats ( n  = 24). Three treatment groups were evaluated in this study: (1) treatment with ointment alone (negative control), (2) treatment with ointment containing 0.2 wt% 4HR, and (3) treatment with ointment containing 2 wt% 4HR. For the assessment of wound healing, digital photographs were taken at 1, 5, and 14 days. Animals were sacrificed at 1, 5, and 14 days for histological examination or ELISA analysis. Results: Western blot analysis showed that TNF-α protein levels were reduced following treatment with 4HR at concentrations between 1 and 10 μg/mL. In animal studies, the average denuded area 14 days after burn was smaller in the 2 wt% 4HR treatment group compared with the control group ( P  = 0.022). Immunohistochemical analysis revealed lower TNF-α expression in the 2 wt% 4HR treatment group compared with the control group 14 days after burn ( P  = 0.027). Conclusion: 4HR reduced TNF-α expression in RAW264.7 cells and in the burn wounds of rats. Burn wounds dressed with ointment containing 4HR also exhibited rapid epithelization and collagen regeneration.